Hormonal regulation of carbohydrate and lipid metabolism under extreme loads in highly-skilled athletes in different sports - Tambovtseva, R. V.; Nikulina, I. A. (Theory and Practice of Physical Culture, 2017)
Objective of the study was to analyze hormonal regulation of carbohydrate and lipid metabolism under extreme loads in highly-skilled athletes in different sports. Subjects were tested by the incremental to submaximal cycle ergometer tests, with their venous blood being tested for insulin, somatotropin, non-esterified fatty acids, glycerin and glucose; and arterial blood tested for lactic acid at rest in the 3 and 10 minutes of recovery; and urine being tested for catecholamine. The incremental to submaximal exercise tests in application to highly-skilled skaters, middle-distance runners and pentathletes showed the following: the general regularities of the body's adaptation to the physical loads in the subjects were associated with some specific aspects of the metabolic processes correlating with the training and competitive load specifics. The tests found some differences in the metabolic processes in athletes specializing in different sport disciplines both at rest and in their bodily responses to loads.